Differential Response of Arkansas Palmer Amaranth (Amaranthus palmeri) to Glyphosate and Mesotrione. (7th September 2018) - Singh, Shilpa; Roma-Burgos, Nilda; Singh, Vijay; Alcober, Ed Allan L.; Salas-Perez, Reiofeli; Shivrain, Vinod
Abstract: We conducted a greenhouse study to evaluate the differential response of Palmer amaranth to glyphosate and mesotrione and to quantify the level of tolerance to mesotrione in recalcitrant (difficult-to-control) accessions and their offspring. Seeds were collected from 174 crop fields (corn, cotton, and soybean) across Arkansas between 2008 and 2016. Palmer amaranth seedlings (7 to 10 cm tall) were treated with glyphosate at 840 g ae ha –1 or mesotrione at 105 g ha –1 . Overall, 47% of the accessions (172) were resistant to glyphosate with 68% survivors. Almost 35% of accessions were highly resistant, with 90% survivors. The majority of survivors from glyphosate application incurred between 31% and 60% injury. Mesotrione killed 66% of the accessions (174); the remaining accessions had survivors with injury ranging from 61% to 90%. Accessions with the least response to mesotrione were selected to determine tolerance level. Dose–response assays were conducted with four recalcitrant populations and their F1 progeny. The average effective doses (ED50 ) for the parent accessions and F1 progeny of survivors were 21.5 g ha –1 and 27.5 g ha –1, respectively. The recalcitrant parent populations were three- to five-fold more tolerant to mesotrione than the known susceptible population, as were the F1 progeny.